TELENURSING MENINGKATKAN KUALITAS HIDUP PASIEN DENGAN PENYAKIT KRONIS: TELENURSING IMPROVE QUALITY OF LIFE AMONG PATIENT WITH CHRONIC DISEASES - Setiawan, Henri; Khaerunnisa, Reffi Nantia; Firdaus, Fidya Anisa; Heryanto, Hery (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Telenursing is a long-distance treatment that utilizes the development of information and communication technology. Telenursing can be used by families who treat patients with chronic illness at home so it can be directed and controlled in their care. The objective of this Literature Review is to explain the effect of telenursing on quality of life among patient with chronic disease. The data were identified from five journal databases including PubMed, JSTOR, Willey Online Library, Sage Journal and Taylor Francis Online by PIOS (Participant, Intervention Outcomes and Study Design) method and MeSH term on advanced search engines. Articles that became research data were published in 2008 to 2020 with English version, opened access and full text in the form of original articles or research articles. There were 2,060 articles found, a screening process was carried out using PRISMA Flowchart to eliminate articles that did not meet the criteria. In this literature review study, 9 articles were found that proved that the use of telenursing interventions could improve patients satisfaction and quality of life. This study reinforced the findings of previous research studies that showed that telenursing was effective to be used in the process of treating patients with chronic diseases